2015
DOI: 10.3813/aaa.918834
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Task Constraints on the Perceptual Evaluation of Violins

Abstract: SummaryResults from twop revious studies that involved free-playing evaluative tasks showed that players are selfconsistent in their preference for violins and tend to agree of what particular qualities theyl ook for in an instrument (int his case, "richness" and "dynamic range"). However, as ignificant lack of agreement between violinists wasobserved, likely because different players evaluate the same perceptual attributes in different ways. The present study thus investigated whether there will be more inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
2
6
1
Order By: Relevance
“…Analyses of intra-individual consistency and inter-player agreement in the (nonverbal) preference and attribute judgments showed that while violinists generally agreed on what particular attributes they look for in an instrument, the perceptual evaluation of the same attributes varied dramatically across individuals, thus resulting in large interplayer differences in the preference for violins. A third experiment [58] and studies by Fritz et al [26,27] and Wollman et al [66,67] reached similar conclusions.…”
Section: Touch and The Conceptualization Of Violin Quality By Musicianssupporting
confidence: 72%
“…Analyses of intra-individual consistency and inter-player agreement in the (nonverbal) preference and attribute judgments showed that while violinists generally agreed on what particular attributes they look for in an instrument, the perceptual evaluation of the same attributes varied dramatically across individuals, thus resulting in large interplayer differences in the preference for violins. A third experiment [58] and studies by Fritz et al [26,27] and Wollman et al [66,67] reached similar conclusions.…”
Section: Touch and The Conceptualization Of Violin Quality By Musicianssupporting
confidence: 72%
“…1 and 2). The emergence of 496 shared conceptualization structures between musicians suggests, in line with our previous findings 497 ( Saitis et al, 2012Saitis et al, , 2015, that interindividual differences in the preference for violins originate (14), light (11), comfortable (8), quick (8), playability (7), flexible (6), ability to create different timbres (6), versatile (4), low action (2), predictable (2), maniable (2), liberty (2), solidité, cushioned, convenient to handle, enough room for control, reflexible, well-adjusted, small, touche agréable, fit bridge, to feel a healthy contact with the bow on the string, répondre au quart de tour, to give a lot back, to take a lot of weight from the bow, to stand up to what the player gives hard to play (5), heavy (3), uncomfortable (3), more effort (3), difficult to play (2), slow (2), missing of the tuning (2), bulky (2), big, gros, awkward, rigid, too light, labored vibrato, big neck, to fight with the instrument [to produce the desired sound]…”
supporting
confidence: 78%
“…Similarly, Lukasik ( 2005 ) suggested associations among spectral centroid with bright/dark, and tristimulus 1 and 3 with deep/full and flat/empty, respectively. Saitis et al ( 2015 ) reported on associations among spectral centroid, tristimulus 2 and 3 with sound richness. Hermes et al ( 2016 ) reported high correlations among harmonic centroid and clarity.…”
Section: Systems For Automatic Assessment Of Music Performancementioning
confidence: 99%